LOW-MODULUS MATERIALS FOR COAXIAL CABLE - Kell,R. M.; Bennett,Bailey; Stickney,P. B. (1966)
Research was conducted to evaluate and develop new materials for both insulation and jacketing. The objective was to improve low-temperature flexibility without sacrifice of the desirable electrical and physical properties of existing cable materials. The conclusions are: (1) There is no single polymer available having the flexibility, resistance to deformation at elevated temperature, and electrical characteristics desired for insulation in coaxial cable for arctic use. (2) The desired balance of properties can be achieved by blending selected resins and elastomers. (3) Vulcanization of the polymer blend improves the physical properties permitting, for example, greater flexibility at low temperature with less sacrifice in high-temperature performance. However, the dielectric properties are adversely affected. (4) Blends consisting of approximately equal parts of high-molecular-weight polyisobutylene with a high-density ethylene copolymer have a good balance of physical properties and are extrudable. These blends appear promising for use as cable insulation and offer an improvement over existing materials. (5) Several new polymers in the polyurethane and ethylene copolymer class have demonstrated acceptable performance as cable jacketing and are more flexible at arctic temperatures than the polyvinyl chloride compositions presently used. (6) The best combination of flexibility, abrasion resistance, tear strength, and resistance to elevated-temperature deformation was exhibited by a millable, thermoplastic polyether urethane elastomer. Prepared for presentation at the Annual Wire and Cable Symposium (15th), Atlantic City, N. J., 7-9 Dec 1966.